2011
DOI: 10.2459/jcm.0b013e328344bcdc
|View full text |Cite
|
Sign up to set email alerts
|

Diving bradycardia: a mechanism of defence against hypoxic damage

Abstract: A feature of all air-breathing vertebrates, diving bradycardia is triggered by apnoea and accentuated by immersion of the face or whole body in cold water. Very little is known about the afferents of diving bradycardia, whereas the efferent part of the reflex circuit is constituted by the cardiac vagal fibres. Diving bradycardia is associated with vasoconstriction of selected vascular beds and a reduction in cardiac output. The diving response appears to be more pronounced in mammals than in birds. In humans, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 69 publications
3
85
2
1
Order By: Relevance
“…These findings contradict what the diving response would have predicted i.e. brady cardia [43], and an elevated blood pressure.…”
Section: Discussioncontrasting
confidence: 55%
“…These findings contradict what the diving response would have predicted i.e. brady cardia [43], and an elevated blood pressure.…”
Section: Discussioncontrasting
confidence: 55%
“…These original landmark studies remain the cornerstone in our understanding of the cardiovascular adjustments required for conserving oxygen and prolonging the duration of submergence by air-breathing vertebrates. In general, the physiological response to submersion is qualitatively similar for aquatically adapted and terrestrial mammals, with diving-induced bradycardia considered to be the major mechanism to regulate blood oxygen depletion rate, thereby conserving oxygen for the brain and heart (Harrison and Tomlinson, 1960;Scholander, 1963;Van Citters et al, 1965;Ridgway et al, 1975;Alboni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In these animals, it has been demonstrated that both apnea alone and facial immersion alone can induce vagal activity, but the combined situation enhances the effects [ 12 ]. Within 10-40 s there is selective vasoconstriction with less perfusion in the peripheral vascular beds of skin, muscles, and viscera.…”
Section: Diving Responsementioning
confidence: 99%